2002
DOI: 10.1016/s1631-0705(02)01415-9
|View full text |Cite
|
Sign up to set email alerts
|

A lightning initiation mechanism: application to a thunderstorm electrification model

Abstract: The use of numerical models has greatly increased our understanding of the electrical and microphysical process within electrified clouds. We use the University of Washington, 1.5dimensional thunderstorm model to examine the effects of including a runaway electron based lightning initiation mechanism. We find that this mechanism can significantly alter the electrification history of modeled storms and produce vertical electric field profiles that are very similar to those of observed storms. To cite this artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…However, this value is larger than the RREA threshold field. Indeed, in situ electric field measurements show that the electric field near the lightning initiation point sometimes exceeds the RREA threshold (Marshall et al 2005) It has been suggested that runaway electron avalanches seeded by cosmic-ray extensive air showers (EASs) could result in enough ionization to initiate lightning (Gurevich et al , 2003Solomon et al 2001Solomon et al , 2002Petersen et al 2008). This hypothesis has gained a great deal of attention in recent years, both from the scientific community and from the popular press (Dwyer 2005a;Gurevich and Zybin 2005).…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…However, this value is larger than the RREA threshold field. Indeed, in situ electric field measurements show that the electric field near the lightning initiation point sometimes exceeds the RREA threshold (Marshall et al 2005) It has been suggested that runaway electron avalanches seeded by cosmic-ray extensive air showers (EASs) could result in enough ionization to initiate lightning (Gurevich et al , 2003Solomon et al 2001Solomon et al , 2002Petersen et al 2008). This hypothesis has gained a great deal of attention in recent years, both from the scientific community and from the popular press (Dwyer 2005a;Gurevich and Zybin 2005).…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…Experiments in the laboratory with hydrometeors immersed in otherwise uniform electric fields have shown evidence that dielectric breakdown could be initiated by the locally enhanced fields of these hydrometeors (Dawson and Duff 1970, Craib and Latham 1974, Solomon et al 2002, Sentman and Christian 2005. Theoretically, a conductive sphere immersed in a uniform field will enhance the local field by a factor of three (Stratton 1941).…”
Section: Possible Interpretations Of the Discrepancy In Field Magnitumentioning
confidence: 99%
“…Electric breakdown in the first stage of the lightning process, and subsequently the discharge propagation at larger scale, have to be considered. At the present time, two distinct hypotheses may be considered as far as the first stage of the lightning discharge is considered: the runaway electron theory (Gurevich et al, 1992;Gurevich et al, 1999;Solomon et al, 2002), and the microphysical hypothesis in which the hydrometeor surfaces may act as corona emission sites (Crabb and Latham, 1974;Griffiths and Latham, 1974;Blyth et al, 1998;Schroeder et al, 1999;Coquillat et al, 2003). In the following, we focus on the microphysical hypothesis since hail is considered.…”
Section: Discussionmentioning
confidence: 99%